1995
DOI: 10.1074/jbc.270.43.25872
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Casein Kinase II by p34cdc2

Abstract: . In the present study, we have demonstrated that a glutathione S-transferase fusion protein encoding the C-terminal 126 amino acids of the ␣ subunit is phosphorylated by p34 cdc2 at the same sites as intact casein kinase II, indicating that the mitotic phosphorylation sites are localized within the C-terminal domain of ␣. Four residues within this domain, Thr-344, Thr-360, Ser-362, and Ser-370, conform to the minimal consensus sequence for p34 cdc2 phosphorylation. Synthetic peptides corresponding to regions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
50
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(51 citation statements)
references
References 51 publications
1
50
0
Order By: Relevance
“…A possible clue is that both subunits of CK2 are extensively phosphorylated by cdc2 kinase during mitosis (34). This is particularly dramatic for the catalytic ␣ subunit where 4 residues in the C-terminal domain are phosphorylated by cdc2 kinase resulting in substantial conformational modifications (35). This is consistent with our in vitro findings that the ability of CK2 to create the MPM-2 epitope is greatly stimulated in the presence of cdc2 kinase, although this FIG.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…A possible clue is that both subunits of CK2 are extensively phosphorylated by cdc2 kinase during mitosis (34). This is particularly dramatic for the catalytic ␣ subunit where 4 residues in the C-terminal domain are phosphorylated by cdc2 kinase resulting in substantial conformational modifications (35). This is consistent with our in vitro findings that the ability of CK2 to create the MPM-2 epitope is greatly stimulated in the presence of cdc2 kinase, although this FIG.…”
Section: Discussionsupporting
confidence: 82%
“…1A, lanes 2 and 3). Since CK2 is extensively phosphorylated by cdc2 kinase during mitosis (34,35), the influence of the simultaneous presence of both CK2 and cdc2 kinase was also determined. The results show that the presence of cdc2 kinase greatly stimulates the ability of CK2 to generate the MPM-2 phosphoepitope on topoisomerase II␣ (Fig.…”
Section: Protein Kinase Ck2 Can Generate the Mpm-2 Epitope Onmentioning
confidence: 99%
See 1 more Smart Citation
“…In 3T3 L1 fibroblast cells, the increased expression of CK2b was shown to cause accumulation in G2/M, suggesting a role of CK2 at this point of the cell cycle (Li et al, 1999). Furthermore, both types of CK2 subunits can be phosphorylated by CDK1 in vitro and in intact cells during mitosis (Litchfield et al, 1992;Bosc et al, 1995). In addition, CDK1 itself can be phosphorylated by CK2 (Russo et al, 1992) and CK2 has been implicated in the phosphorylation of cyclin B, which regulates its nuclear translocation (Li et al, 1997b).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been demonstrated that CK2␣, but not CK2␣Ј, is phosphorylated in mitotic cells of mammalian and avian origin (16), suggesting that the functions of the two isoforms are independently regulated during cell division. The mitotic sites of phosphorylation of CK2␣ were identified as Thr 344 , Thr 360 , Ser 362 , and Ser 370 , all of which are located within the carboxyl-terminal domain of CK2␣ (17). There is also a "PXXP" motif adjacent to two of the phosphorylation sites.…”
mentioning
confidence: 99%